Case report: Diagnosis and treatment of DGAT1 deficiency-induced congenital diarrhea in two cases and literature review - Li, Jian; Sun, Mei; Guo, Jing; Xu, Lingfen (Frontiers in Pediatrics, 2023)
Introduction: Congenital diarrhea is a rare inherited intestinal disease characterized by persistent and severe diarrhea and malabsorption in the first few weeks after birth, which can be life-threatening. Some congenital diarrheal diseases are associated with mutations in the diacylglycerol acyltransferase 1(DGAT1) gene. Case Descriptions:This study delineated 2 cases of diarrhea and growth retardation, subsequently confirmed as congenital diarrhea via genetic testing, revealing that the etiology involved compound heterozygous mutations in the DGAT1 gene. Diagnostic Assessments: High-MCT milk powder did not obtain an ideal outcome, whereas lowfat diets improved the symptoms of diarrhea and increased the body weigths.The two cases facilitated our understanding of the clinical features of, and treatments for, patients harboring a DGAT1 mutation and enriched the existing DGAT1 mutation database.